Identification of physical and visual enclosure of landscape space units with the help of point clouds. Issue 3 (2nd July 2020) - Wang, Yijing; Cheng, Yuning; Zlatanova, Sisi; Palazzo, Elisa
ABSTRACT: Vertical enclosure is incapable of describing the permeation of landscape space enclosures. Physical and visual enclosures are identified to compensate for enclosure cognition inadequacies. Physical enclosures reflect the restriction of behavior, and visual enclosures embody the viewshed extension range. An identification method is proposed and implemented using point cloud data. Multiple enclosures are mapped, and the distribution of each enclosure is shown. Seven combinations are summarized based on the organization of vertical, physical, and visual enclosures. Four typical physical and visual enclosing modes are defined by the quadrant distribution of quantified enclosure features. From the identification to the distribution extraction and typical type identification, this research transforms descriptive enclosures into identifiable multiple enclosures that can be computed and quantified.